2002
DOI: 10.1002/1099-0682(200210)2002:10<2710::aid-ejic2710>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Characterisation of New Phenolato-Bridged Manganese Complexes [L2Mn2]2+ − Formation by Ligand Oxidation in LaH [LaH = N-(2-hydroxybenzyl)-N,N′-bis(2-pyridylmethyl)ethane-1,2-diamine]

Abstract: A mononuclear [L a Mn III OAc](ClO 4 )·0.5H 2 O [2(ClO 4 )·0.5H 2 O] complex with a new amino-containing pentadentate ligand L a H with a [N 4 O] coordination sphere has been obtained. Magnetic susceptibility measurements of 2(ClO 4 )·0.5H 2 O indicated a high spin electronic configuration for the Mn III ion.In cyclic voltammetry the reversible wave observed at E 1/2 = 0.15 V vs. SCE was attributed to the reduction of Mn III into Mn II . In acetonitrile solution complex 2 spontaneously evolved into phenolato-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
22
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
(32 reference statements)
7
22
2
Order By: Relevance
“…The fourth is considerably longer, probably due to the Jahn-Teller effect, with an Mn1-O1 distance of 2.215(2) Å , which is close to the axial bond in a related pentaphenolato Mn III -Mn III complex [14]. The equatorial Mn-N distances (2.089-2.146) are in the range observed for a series of similar Mn III complexes [14,17,19] and about 0.1 Å shorter than in related Mn II complexes [16,18].…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The fourth is considerably longer, probably due to the Jahn-Teller effect, with an Mn1-O1 distance of 2.215(2) Å , which is close to the axial bond in a related pentaphenolato Mn III -Mn III complex [14]. The equatorial Mn-N distances (2.089-2.146) are in the range observed for a series of similar Mn III complexes [14,17,19] and about 0.1 Å shorter than in related Mn II complexes [16,18].…”
mentioning
confidence: 68%
“…A Mn V @O moiety has been proposed to play a key-role in OAO bond formation in photosynthesis as well as a model complex [9][10][11]. It is therefore of interest to study and characterize highvalent dinuclear manganese complexes, and we and others have prepared a number of dinuclear manganese complexes, which have oxidation states between Mn II and Mn IV and a varied number of coordinating phenoxy groups, which could be expected to stabilize high oxidation states of manganese [12][13][14][15][16][17][18]. These studies include the dinuclear Mn II,III complex 3, which was first prepared by Hendrickson et al [19] This complex was found to give a fairly stable Mn III,IV complex, which, however, appears to decompose on further oxidation [20,21].…”
mentioning
confidence: 99%
“…Such a type of link between divalent Mn centers has been reported to lead to both, ferro- [31,[36][37][38][39] and antiferromagnetic interactions. [40][41][42][43] The actual magnetic behaviour depends strongly on the efficiency of the overlap between d x 2 -y 2 orbitals of the metal ions through the phenoxide Odonors, which is considered the main pathway to antiferromagnetism. In 1, the latter is expected to be much reduced, given the weakening of antiferromagnetic pathways that might be caused by the severe distortion in the coordination geometry shown by the metal ions.…”
Section: (Py) 5 ] (1) Which Displays An Un-mentioning
confidence: 99%
“…The Mn(II) ion is in a distorted octahedral environment. Therefore, according to the ligand field theory and assuming an O h symmetry, the ground state of manganese(II) is 6 A 1g . Because d-d transitions of Mn(II) ( 6 A 1g !…”
Section: Ir and Uv-vis Spectroscopymentioning
confidence: 99%
“…Consequently, polydentate N,O-containing ligands are continuously developed both to prepare catalysts, and to model the active site of enzymes [5,6].…”
Section: Introductionmentioning
confidence: 99%